"Turning green into gold": a framework for energy performance contracting (EPC) in China's real estate industry. (16th December 2015) - Zhang, Xiaoling; Wu, Zezhou; Feng, Yong; Xu, Pengpeng
Abstract: There is a growing interest in a sustainable built environment and green technologies are gaining worldwide attention. However, implementing green technologies usually requires more investment than using traditional technologies and the payback period tends to be very long. In China, most developers sell their properties and subsequently transfer the ownership to customers. Hence, a crucial problem for promoting green construction is that developers cannot obtain economic profits ("gold") from implementing "green" technologies. Meanwhile, other stakeholders, such as property management companies, are also hesitant to adopt green technologies because of the large investment involved and their lack of experience. To tackle this problem, an energy performance contracting (EPC) based framework is proposed, to turn "green" investment into "gold" benefit by careful sharing of the risks existed. The framework was developed by conducting a focus group meeting with three experienced representatives from developer, property management company and energy service company respectively. A real-life case study, which includes both energy efficient system retrofit and new construction, is used to estimate the costs and benefits involved to demonstrate and verify the conceptual framework. The results show that the proposed framework can support the application of green technologies in both types of projects. Economic benefits as well as environmental benefits can be gained for the project stakeholders and the whole society.